PENINGKATAN VIABILITAS DAN VIGOR BENIH PADI SAWAH (Oryza sativa L.) DENGAN TEKNIK BIOMATRICONDITIONING - Stefany Darsan; Gusti Ayu Kade Sutariati; Sarawa Mamma (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2018)
This research was aimed to examine and get biomatriconditioning technique that increase viability and seed vigor rice (Oryza sativaL.). This research was conducted at Agronomi Unit of the Laboratory Agrotechnology of Haluoleo University, Kendari from January until March 2013. This research used completely randomized design with factorial. The first factor was the variety: Konawe and Inpari 10, the second factor was biomatriconditioningtechnique Control, Bacillus CKD061+Husk Charcoal Powder, Bacillus CKD061+Powder Red Brick. Serratia CMN 175 + Husk Charcoal Powder, Serratia CMN175+Red Brick powder. For the all numbers there were 14 combination treatments, repeated for 3 times, so the total of experimental units were 42. Replication consisted of 5 polybag so there were 210 plants. Data were analyzed using a manner sidik, followed by Test Honestly Significant Difference. The results showed that the best biomatriconditioning for Konawe varieties was Serratia CMN175 + rice husk powder treatment, while for the Inpari varieties 10 Bacillus CKD061 + husk powder for the both of treatment could be able to improve simultaneity grow, vigor index, relative growth speeds, T50, plant height and number of tillers.Keywords: Bacillus CKD061, P. fluorescensPG01, seed of rice, Serratia